Child socioemotional behavior and adult temperament as predictors of physical activity and sedentary behavior in late adulthood - Johanna Ahola; Katja Kokko; Lea Pulkkinen; Tiia Kekäläinen (BMC Public Health, 2023)
Abstract Background Most studies investigating the association of temperament with physical activity and sedentary behavior have examined children or adolescents, employed cross-sectional or longitudinal designs that do not extend from childhood into adulthood, and utilized self- or parent-reported data on physical activity and sedentary behavior. This longitudinal study investigated whether socioemotional behavior in childhood and temperament in middle adulthood predict accelerometer-measured physical activity and sedentary behavior in late adulthood. Methods This study was based on the Jyväskylä Longitudinal Study of Personality and Social Development (JYLS). Socioemotional behavior (behavioral activity, well-controlled behavior, negative emotionality) was assessed at age 8 based on teacher ratings, whereas temperament (surgency, effortful control, negative affectivity, orienting sensitivity) was assessed at age 42 based on self-rating. Moderate-to-vigorous physical activity and sedentary behavior were assessed at age 61 using an accelerometer. Data (N = 142) were analyzed using linear regression analysis. Results In women, behavioral activity at age 8 predicted higher levels of daily sedentary behavior at age 61. The association did not remain statistically significant after controlling for participant’s occupational status. In addition, women’s negative affectivity at age 42 predicted lower daily moderate-to-vigorous physical activity at age 61, particularly during leisure time. No statistically significant results were observed in men. Conclusions Although few weak associations of socioemotional behavior and temperament with physical activity and sedentary behavior were detected in women, they were observed over several decades, and thus, deserve attention in future studies. In addition to other factors contributing to physical activity and sedentary behavior, health professionals may be sensitive to individual characteristics, such as a tendency to experience more negative emotions, when doing health counseling or planning for health-promoting interventions targeting physical activity and sedentary behavior.